Evaluation of the Aboriginal and Torres Strait Islander Mental Health First Aid Program - Andrew Day; Sharon Casey; Mercy Baird; Lynore Geia; Rosemary Wanganeen (Elsevier, 2021)
Abstract Objective: This study reports findings from an uncontrolled evaluation of a course designed to educate participants in how to recognise and respond to mental health problems until professional help is received. Methods: Utilising a mixed methods design, participants in 21 different courses, delivered across two Australian states, were invited to complete pre‐, post‐, and follow‐up surveys and provide qualitative feedback on their training experiences. Results: Participants reported feeling more confident in their capacity to respond appropriately to a person presenting with a mental health need and believed they would be more likely to provide assistance. Satisfaction was attributed to the skills and sensitivities of instructors who had lived experience of mental health concerns in Aboriginal and Torres Strait Islander communities. Conclusion: This course holds promise in improving mental health literacy in relation to Aboriginal and Torres Strait Islander mental health. Implications for public health: Few courses are available that address issues relating to the social and emotional wellbeing of Aboriginal and Torres Strait Islander People. This study illustrates how community engagement with primary health and specialist mental health services might be strengthened.